Análise da relação do polimorfismo do gene ervw-1 (rs4727276) com a patogênese da pré-eclâmpsia em mulheres do nordeste brasileiro - Fontelles, Gelton (2024)
Preeclampsia (PE) is a multisystem syndrome that can occur during pregnancy. It’s one of the main causes of maternal, fetal and neonatal mortality during pregnancy. Its causes are unclear and the mechanisms underlying its etiopathogenesis remain poorly understood. The hypothesis that the causes of PE are at least partially genetic is widely suggested. Thus, it is important to identify molecular biomarkers that detect it, such as through polymorphisms of the ERVW-1 gene, related to the placentogenesis process. In this sense, the objective of this study was to determine whether the rs4727276 polymorphism of the ERVW-1 gene would be associated with PE in women from the northern region of the State of Ceará, Brazil. For this, clinical data and genetic material mouth scraping were collected from patients admitted in the Sant'Ana Maternity Hospital of Holy House of Mercy Hospital of Sobral divided into two groups: (1) pregnant women with PE (cases, n=64) and (2) normotensive pregnant women (controls, n=76). The laboratory test was performed using the RT-qPCR technique by genotyping to identify the rs4727276 polymorphism related to the ERVW-1 gene in the collected samples. Statistical analyzes were performed using SigmaPlot® software version 11.0 (SYSTAT. Software Inc.) and data presented as mean ± standard error of the mean (SEM). In terms of genotypic distribution and allele frequency, a significant difference was observed in the genotype distribution (CC vs CG+GG/CG vs CC+GG) between the PE and Control groups (p = 0,011; p = 0,05, respectively) indicating a greater expression in PE for the respective genotypes. However, it was not related to the disease severity or the time of onset. It is concluded that the rs4727276 polymorphism of the ERVW-1 gene demonstrated a strong association with PE in a population of women from the Brazilian Northeast. Furthermore, it can be considered a molecular biomarker in the pathophysiology of pre-eclampsia in women, enabling the identification of risk factors for the disease and early detection.